Huldenummer Prof. dr. A. Hacquaert - De Coninck, L.; Dekeyser, W.; De Ridder, M. (Gent: Walschot, 1977)
"L. De Coninck, W. Dekeyser, M. De Ridder, Etc. Themanummer van Natuurwetenschappelijk tijdschrift"